Harmony with Nature in Children’s Fantasy: Palemahan Values in Lucy Pevensie’s Characterization in Prince Caspian - Putu Anggi Yumika Shanti; Ni Komang Arie Suwastini; I Nyoman Pasek Hadi Saputra; Zhu Minxia; Ni Nyoman Artini (English Department, Universitas Negeri Surabaya, 2025)
This present study explored the representation of environmental harmony in Prince Caspian by C.S. Lewis through the lens of local framework, Palemahan derived from Balinese philosophy called Tri Hita Karana. Former studies in Prince Caspian mostly utilized moral, religious, or western eco-critical perspectives, that tend to view environments or nature as objects that need to be protected or managed, while overlooking local philosophical views that regard nature as a living and sacred partner in human existence. This study therefore applies Palemahan as an alternative interpretative lens, employing qualitative interpretive data analysis with an interactive model proposed by Miles, Huberman, and Saldana (2014). The data were obtained from a close reading of the 2008 HarperCollins e-book of Prince Caspian, focusing on Lucy Pevensie’s characterization and her interactions with the natural environment. The findings show Lucy’s engagement with the environment reflects Palemahan values through the affectionate gesture, respect, and emotional connection rather than obligation or domination. Her relationship with the environment emerged from the harmonious feeling from within, aligned with the Palemahan view that see nature carries a sacred presence. Conceptually, this study highlights Tri Hita Karana, particularly Palemahan as the interpretative framework that is meaningful in literary analysis. Pedagogically, the findings suggest that children’s literature can introduce environmental awareness rooted in harmony, not merely responsibility.